The G20 financial reform agenda after five years - Nicolas Véron (Bruegel, 2014)
Five years ago, the declarations of the G20 in landmark leaders' summits in London and Pittsburgh listed specific commitments on financial regulatory reform. When measured against these declarations, as opposed to the surrounding rhetorical hype, most (though not all) commitments have been met to a substantial degree. However, the effectiveness of these reforms in making global finance more stable is not so far proven. This uncertainty on impact mirrors the absence of an analytical consensus on the 2007-08 financial crisis itself. In addition, unintended consequences of the reforms are appearing gradually, even as their initial implementation is still unfinished. At a broader level, the G20 has established neither an adequate institutional infrastructure nor a consistent policy vision for a globally integrated financial system. This shortcoming justifies increasing concerns about economically harmful market fragmentation. One key aim should be to make international regulatory bodies more representative of the rapidly-changing geography of global finance, not only in terms of their membership but also of their leadership and location.
Keywords: 330